2017
DOI: 10.18632/oncotarget.18084
|View full text |Cite
|
Sign up to set email alerts
|

Long working hours, job satisfaction, and depressive symptoms: a community-based cross-sectional study among Japanese employees in small- and medium-scale businesses

Abstract: Although long working hours have been suspected to be a risk factor for depressive symptoms (DS), it is not well understood the conditions under which long working hours are associated with it. This study investigated the moderating effect of job satisfaction on the relationship between working hours and DS. A total of 2,375 full-time non-shift day workers (73% men), aged 18–79 (mean 45) years, in 296 small- and medium-scale businesses were surveyed using a self-administered questionnaire evaluating working ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 59 publications
4
20
0
Order By: Relevance
“…A previous study indicated that long working hours are associated with an increased risk of depression in Japan. Our multiple linear regression analysis showed similar results [23]. Twenge et al [24] reported that the prevalence of depression increased slightly in the United States from April 2020 to May 2020.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A previous study indicated that long working hours are associated with an increased risk of depression in Japan. Our multiple linear regression analysis showed similar results [23]. Twenge et al [24] reported that the prevalence of depression increased slightly in the United States from April 2020 to May 2020.…”
Section: Discussionsupporting
confidence: 85%
“…A previous study indicated that long working hours are associated with an increased risk of depression in Japan. Our multiple linear regression analysis showed similar results [ 23 ].…”
Section: Discussionsupporting
confidence: 78%
“…Fatigue resulting from long working hours is associated with impaired response time,8 16 17 vigilance/alertness,8 18 the ability to process information8 and muscle strength19; however, there are studies showing that long working hours have no impact on psychomotor functioning 20–23. In addition, long shifts in manual labour jobs are associated with lower job satisfaction,24 absenteeism25 26 and a decline in overall health 27…”
Section: Introductionmentioning
confidence: 99%
“…The present findings, i.e., the prevalence of those having depressive symptoms and its association with cancer history, little changed even when the cut-off score of our modified CES-D scale was set at 7 or higher as a research group previously proposed (data not shown) [50]. Previous studies addressing full-time workers in Japan, who were supposed to feel very stressed, found a higher prevalence of CES-D-assessed depressive symptoms, with 25% and 34% in men and women, respectively, in one study [51], and 30% (male subjects: 73%) in another [52]. We thus believe our modified CES-D scale appropriate for evaluating the prevalence of those having depressive symptoms.…”
Section: Presence Of Depressive Symptomsmentioning
confidence: 99%